Two-stage surgical treatment of cataracts with weakness of the lenticular zonular apparatus and uncompensated glaucoma - E.A. Ivachev; S.A. Kochergin (РМЖ "Клиническая офтальмология")
E.A. Ivachev1,2, S.A. Kochergin3 1Penza State University, Penza, Russian Federation 2Clinical Hospital "RZD-Meditsina" of the city of Penza, Penza, Russian Federation 3Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation Aim: to improve the hypotensive effect of trabeculectomy in patients with uncompensated glaucoma and weak lenticular zonular apparatus by preventing intraoperative vitreous body (VB) prolapse. Patients and Methods: all the patients were divided into 3 groups: Group 1 (n=24) - the first stage was trabeculectomy, the second one represented phacoemulsification with an intraocular lens (IOL) implantation; Group 2 (n=29) initially underwent lensectomy followed by trabeculectomy; Group 3 (n=39) experienced lensectomy and, then, trabeculectomy as per the proposed technique. Initial stages of trabeculectomy were performed according to the conventional procedure. After cutting out a deep scleral flap without penetration into the anterior chamber, a cohesive viscoelastic was injected using a cannula under the iris through corneal paracentesis already formed during phacoemulsification into the area of the posterior chamber in the projection of the future coloboma and fistula; then, the internal scleral flap was removed with the opening of the anterior chamber, the iris was inserted into the fistula, after that, the coloboma was formed; a part of viscoelastic was evacuated through the fistula without VB prolapse. By pushing the VB into the vitreal cavity with viscoelastic, the VB prolapse into the formed fistula was prevented. Interrupted sutures were placed on the sclera and conjunctiva. The postoperative follow-up was 24 months. Results: аs for the Group 1, the best corrected visual acuity (BCVA) improved from 0.31±0.1 to 0.41±0.05, and IOP decreased from 25.3±1.1 to 19.3±0.9 mmHg. Complications: intraoperative ocular hypertension — 3 (12.5%), VB prolapse during trabeculectomy — 8 (33.3%), hyphema — 5 (20.8%), ciliochoroidal detachment (CCD) — 4 (16.7%), IOL subluxation — 3 (12.5%). In the Group 2, BCVA improved from 0.29±0.07 to 0.34±0.07, and IOP decreased from 26.8±1.6 to 18.7±0.4 mmHg. Complications: intraoperative ocular hypertension — 1 (3.4%), VB prolapse during trabeculectomy — 3 (10.3%), hyphema — 8 (27.6%), CCD — 6 (20.7%), IOL subluxation — 2 (6.9%). In the Group 3, BCVA improved from 0.34±0.09 to 0.41±0.08, and IOP decreased from 25.9±1.3 to 18.3±0.7 mmHg. Complications: intraoperative ocular hypertension — 1 (2.6%), VB prolapse during trabeculectomy — 0, hyphema — 7 (17.9%), CCD — 6 (15.4%), IOL subluxation — 1 (2.6%). Conclusion: the proposed technique of VB pressing with viscoelastic in the area of absence of the zonules of Zinn during trabeculectomy reduced VB prolapse risk, decreased a number of complications and improved the hypotensive effect. Keywords: glaucoma, cataract, phacoemulsification, trabeculectomy, intraocular lens, intraocular pressure. For citation: Ivachev E.A., Kochergin S.A. Two-stage surgical treatment of cataracts with weakness of the lenticular zonular apparatus and uncompensated glaucoma. Russian Journal of Clinical Ophthalmology. 2024;24(4):177–184 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-3